2018
DOI: 10.1186/s12863-018-0664-1
|View full text |Cite
|
Sign up to set email alerts
|

High resolution melting curve analysis enables rapid and reliable detection of G6PD variants in heterozygous females

Abstract: BackgroundLike glucose-6-phosphate dehydrogenase (G6PD) deficient hemizygous males and homozygous females, heterozygous females could also manifest hemolytic crisis, neonatal hyperbilirubinemia or kernicterus upon exposure to oxidative stress induced by certain foods such as fava beans, drugs or infections. Although hemizygous males and homozygous females are easily detected by conventional G6PD enzyme assay method, the heterozygous state could be missed by the conventional methods as the mosaic population of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…High-resolution melting (HRM) methodology represents a significant advancement in mutation detection over the years. The HRM method has been established for the detection of variants of the beta-globin gene in thalassemia patients and G6PD deficiency in Bangladesh [24, 35].…”
Section: Discussionmentioning
confidence: 99%
“…High-resolution melting (HRM) methodology represents a significant advancement in mutation detection over the years. The HRM method has been established for the detection of variants of the beta-globin gene in thalassemia patients and G6PD deficiency in Bangladesh [24, 35].…”
Section: Discussionmentioning
confidence: 99%
“…With simple design and easy interpretation, our HRM assays can be optimized, and the desired G6PD mutations can be included to enable G6PD genotyping in other areas. In fact, previous studies using different designs and more complicated result analyses demonstrated that HRM assays can detect zygosity in samples ( Yan et al, 2010 ; Islam et al, 2018 ); however, those tests could detect only 1‒2 mutations in a single reaction, making them impractical for use with large sample sizes. The currently available G6PD genotypic platforms appear to have similar limited applications; they are either expensive, time-consuming, or complicated.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, qualitative methods can correctly identify hemizygous male individuals and homozygous female individuals. However, studies have found that heterozygous female individuals are incorrectly classified as G6PD normal by routine qualitative tests ( Chu et al, 2017 ; Islam et al, 2018 ). Female individuals who are heterozygous for G6PD deficiency exhibit a wide range of G6PD activity levels because they have mixed populations of normal and G6PD-deficient RBCs due to random X-inactivation during embryonic development ( Harper, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…G6PD deficiency diagnosis can be made in women homozygous for G6PD gene mutations [89,95]. Moreover, women heterozygous for G6PD gene mutations may give birth to hemizygous male infants who could develop hemolytic crisis upon inadvertent exposure to oxidative stress, which could induce kernicterus, hyperbilirubinemia, and even death [96].…”
Section: Diagnosismentioning
confidence: 99%